1991
DOI: 10.1038/sj.bdj.4807521
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind placebo-controlled comparison of the analgesic effects of single doses of lornoxicam and aspirin in patients with postoperative dental pain

Abstract: The pain experienced after third molar surgery was used as a model to evaluate the analgesic efficacy of a new non-steroidal anti-inflammatory drug, lornoxicam, in a Phase II study. One hundred and fifty fit, young adults participated in this randomised, single dose, double-blind, parallel group clinical study. Three doses of lornoxicam (2 mg, 4 mg, and 8 mg) were compared with aspirin 650 mg and placebo. Patients suffering from moderate to severe pain following surgery were monitored for up to 8 hours. All in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…According to the pertinent literature, the efficacy of lornoxicam has been shown for various surgical indications [9][10][11] as well as dental surgery [8,12,13]. Furthermore, it has been successfully used in the treatment of painful inflammatory musculoskeletal conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…According to the pertinent literature, the efficacy of lornoxicam has been shown for various surgical indications [9][10][11] as well as dental surgery [8,12,13]. Furthermore, it has been successfully used in the treatment of painful inflammatory musculoskeletal conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…tended to give better pain relief than aspirin (a single dose of 650 mg p.o.) in patients after dental surgery [3].…”
Section: Discussionmentioning
confidence: 99%
“…Lornoxicam is a new compound combining the potency of the oxicams with a reduced risk of side effects. In comparison with other oxicams, lornoxicam has a relatively short elimination halflife (3 to 5 h [2]) and good gastrointestinal tolerability [3][4][5] which is an advantage in terms of less side effects than other oxicams. Like other NSAIDs, the anti-inflammatory/ analgesic activity of lornoxicam is related to the inhibitory action on prostaglandin synthesis, via inhibition of cyclooxygenase (COX) activity in the COX pathway of arachidonic acid metabolism [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with other oxicams, lornoxicam has a relatively short elimination half-life (3-5 h [2]) and good gastrointestinal tolerability [3][4][5] which is an advantage in terms of fewer sideeffects than other oxicams. Potent anti-inflammatory and analgesic activities of lornoxicam in both animalmodels [2] and clinical trials [3][4][5][6][7] have been reported. In animal studies, lornoxicam had anti-inflammatory (carrageenan oedema) and analgesic (writhingtest) activity about 10 timesgreaterthan that oftenoxicam [2].…”
mentioning
confidence: 99%